Cost Analysis and Working Methods for Balcony Railings in Multi-Storey Buildings - Pangestu, Rizky Yoga; Anisah, Anisah; Handoyo, Santoso Sri (Journal of Engineering Education and Pedagogy, 2023)
This article discusses cost analysis and methods for working on balcony railings in multi-storey buildings. Balcony railings are an important element in the design and safety of high-rise buildings, as they protect occupants from falls and provide an attractive aesthetic appearance. Therefore, it is important to ensure that the installation of balcony railings complies with applicable planning standards. By exploring information about material costs, work costs, construction efficiency, and other factors that influence the choice of railing form, this research will provide construction professionals with more informed guidance in decision making. In addition, this analysis will also open a window to better understand how the choice of railing shape can affect the project timeframe and the final result of the building.